Polemik Haluan Negara Bagi Presiden - Efriza, Efriza (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2017)
This paper explains the problem between the State Policy and the Outlines of State Policy (GBHN), which also explains the differences between the 1945 Constitution before and after the amendment. After the Amendment to the 1945 Constitution has placed the principle of constitutional supremacy replacing parliamentary supremacy. But the polemic is present in the community, regarding the absence of State Policy that the state's development plan is considered inconsistent and sustainable because it is only based on the vision and mission of the presidential candidates during the campaign. While the desire to bring back the GBHN is because it considers that with the existence of the GBHN, the country's strategic development is no longer determined by the tastes and interests of the regime it self. DAFTAR PUSTAKA BukuAsshiddiqie, Jimly, Konstitusi dan Konstitusionalisme Indonesia, Jakarta: Sinar Grafika, 2014.Bo’a, Fais Yonas, UUD 1945 MPR dan Keniscayaan Amandemen: Terkait Kewenangan Konstitutif MPR dan Kebutuhan Amandemen Kelima UUD 1945, Yogyakarta: Pustaka Pelajar, 2018.Gaffar, Janedjri M., Demokrasi Konstitusional: Praktik Ketatanegaraan Indonesia Setelah UUD 1945, Jakarta: Konpress, 2012.Nazir, M., MetodePenelitian, Jakarta: Ghalia Indonesia, 2003.Nurdin, Nurliah, Komparasi Sistem Presidensial Indonesia dan Amerika Serikat Rivalitas Kekuasaan Antara Presiden dan Legislatif (2004-2009), Jakarta: MIPI, 2012.Mas, Marwan, Hukum Konstitusi dan Kelembagaan Negara, Depok: Rajagrafindo Persada, 2018.Rohaniah, Yoyoh, dan Efriza, Pengantar Ilmu Politik: Kajian Mendasar Ilmu Politik, Malang: Intranspublishing, 2016. JurnalBiro Pengkajian MPR (Eds), Penguatan Sistem Demokrasi Pancasila, Jakarta: Badan Pengkajian MPR RI, 2017.Indra J. Piliang, dan T.A. Legowo, (Eds), Disain Baru Sistem Politik Indonesia, Jakarta: Centre for Strategic and International Studies, 2006.Moch. Nurhasim, Pembangunan Nasional Bukanlah Produk Rezim, dalam Jurnal Majelis, Haluan Negara Sebagai Arah dan Sasaran Pembangunan Nasional. Edisi 02/Februari 2018. Data KualitatifHasil Wawancara, Maswadi Rauf, Ketua Tim Ahli Bidang Politik PAH I BP MPR 1999-2002, dan Dosen Ilmu Politik di Universitas Nasional (Unas), 19 Desember 2015, Jakarta.Hasil Wawancara, I Made Leo Wiratma, ahli hukum tata negara dan peneliti Forum Masyarakat Peduli Parlemen Indonesia (Formappi), tanggal 21 Desember 2015, Jakarta.Wawancara by phone, Sulardi, Dosen Hukum Tata Negara, di Universitas Muhammadiyah Malang, tanggal 31 Desember 2015.